Aportaciones y pervivencias en las ciudades de América. Un estado de la cuestión - Luis María Calvo (Mélanges de la Casa de Velázquez, 2023)
The process of Spanish settlement and foundation of cities in America began in the late fifteenth century, when modernity had broken into Europe and the elements of the new culture coexisted with practices and ideas from the medieval world. In this context, the conquistadors set out to transplant in the different American spaces their culture, still at a crossroads of mutation and transformation, between medieval persistence and Renaissance modernity. From its confrontation with regional cultures, a different and original culture will emerge, nourished by American and European, pre-Hispanic, medieval and Renaissance contributions.This article proposes a historiographical review that focuses attention on the persistence of medieval ideas and practices that contributed to the construction of Latin America, and that were present in the process of settlement, in the configuration of the urban layout and in the generation of its architecture.